Evaluating the technical and economic viability of 3-hydroxypropionic acid production from biomass - Muhammad Umer; Caterina Brandoni; Angela Rolfe; Neil Hewitt; Jikai Zhao; Seyedamirreza Babaei; Eun Joong Oh; Adriana Cunha Neves; Ye Huang (Biomass and Bioenergy, 2027)

Optimization and Evaluation of Aceclofenac Loaded Solid Lipid Nanoparticles via Response Surface Methodology - Khadija Saleem; Nariman Shahid; Badarqa Tul Ayesha; Alia Erum; Amna Wajdan; Kashif Barkat; Ume Ruqia Tulain; Muhammad Umer Ashraf; Sana Hanif (Journal of Pharmaceutical Innovation, 2027)

Core genome analysis reveals novel drug and vaccine targets in multidrug-resistant Citrobacter koseri - Zubda Ashraf; Fizza Arshad; Samina N. Shakeel; Faiz Ur Rahman; Khaled Fahmi Fawy; Sarah A. Altwaim; Saeed M. Alasmari; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Genetic dissection and QTL validation of seedling root system architecture in Chinese wheat landraces - Hafiz Muhammad Faisal Umer; Muhammad Junaid Jalil; Huaping Tang; Hang Liu; Md Nahibuzzaman Lohani; Qiang Xu; Zhi Zheng; Yaxi Liu; Jirui Wang; Guoyue Chen; Qiantao Jiang; Yuming Wei; et al. (Euphytica, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Synthesis and application of NiFe2O4/Nb2C-MXene composites for enhanced microbial fuel cell performance in wastewater treatment: Advancing sustainable bioelectricity generation - Muhammad Waseem Mumtaz; Haseeb Ashraf; Hamid Mukhtar; Memona Sadiqa; Uroosa Saeed; Waheed Miran; Tahir Iqbal; Aashir Waleed; Umer Rashid (Biomass and Bioenergy, 2026)

Exogenous hesperidin orchestrates antioxidant defense, osmolyte metabolism, and nutrient homeostasis to mitigate heavy metal toxicity in canola - Sherjeel Hashmat; Humaira Yasmeen; Bakhrom Jobborov; Muhammad Imran; Mohammed S. Alotaibi; Hossam S. El-Beltagi; Usman Zulfiqar; Amna Batool; Umer Farooq (BioMetals, 2026)

Integrative mechanisms of photoperiod and temperature regulation in insect diapause - Dilawar Abbas; Kamran Haider; Farman Ullah; Muhammad Yasir Ali; Umer Liaqat; Maolin Hou (Journal of Pest Science, 2026)

Editorial Expression of Concern: Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Breakthrough advances in plant stress physiology: Acinetobacter schindleri SR-5–1 mitigates wastewater-induced nutrient imbalances in linseed plants - Sherjeel Hashmat; Umer Farooq; Muhammad Tariq Javed; Anni Maryam Afzal; Mohsin Raza Bukhari (Biologia, 2026)

Chronic ischemic heart disease and co-recorded depression on death certificates: national mortality trends in the United States - Sarim Hassan Shahab; Muhammad Uzair Afzal; Kanza Zainab; Esha Umair; Hadia Ghazala Masood; Umer Abdur Rahman (Next Research, 2026)

Recent developments in design and fabrication of ZIF-based materials for CO2 mitigation and environmental remediation - Hafsa Khalid; Aimon Saleem; Umer Younas; Parveen Akhter; Heena Ameen; Faisal Ali; M.I. Khan; Muhammad Pervaiz (Journal of Environmental Management, 2026)

Diesel engine performance enhancement using MXene nano-additives: An experimental study on efficiency and Pollutant Suppression - Mohd Danish; Sajid Ali; Syed Mohd Yahya; Rashid Ali; Suhaib Umer Ilyas; Sami Mansour Ghazali; Muhammad Faisal Rathore; Saeed Rubaiee (Fuel, 2026)

Multifunctional MXene film–embedded GFRP composites: Enabling EMI shielding and efficient electrothermal de-icing - Muhammad Yasir Khalid; Abdallah Kamal; Dawei Zhang; Lianxi Zheng; Kin Liao; Kamran Ahmed Khan; Rehan Umer (Chemical Engineering Journal, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Morphology and phylogeny reveal a New Species and Two New Combinations of Xerocomellus (Boletaceae) from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Syed Mohammad Tauseeq Ali Shah; Dege Zheng; Umer Rehman; Atika Noor; Muhammad Asif; Dong-Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (Current Microbiology, 2026)

Biomedical applications of fungal-derived nanoparticles: bridging mycology and nanotechnology for next-generation therapeutics - Umer Rehman; Mohsin Ullah; Syed Mohammad Tauseeq Ali Shah; Muhammad Adnan; Ishtiaq Ahmad; Zabta Khan Shinwari (Plant Biosystems, 2026)

Winter canola integration improves carbon balance, biomass, and profitability in illinois corn–soybean systems - Muhammad Umer Arshad; Soonho Hwang; Chunhwa Jang; Heesu Jeon; DoKyoung Lee (Agricultural Systems, 2026)

Valorization of rubber waste for the synthesis of an acidic heterogeneous catalyst for efficient palm fatty acid distillate esterification - Muhammad Aliyu; Junaid Ahmad; Chawalit Ngamcharussrivichai; Kamil Kayode Katibi; Syed Ahmar Ali Hashmi; Umer Rashid (Process Safety and Environmental Protection, 2026)

Metabolomic profiling and identification of flavonoids related compounds in peanut seed oils for inhibition of aspergillus flavus growth - Lingling Wu; Weinan Xu; Xinyang Wang; Muhammad J. Umer; Weicai Jin; Zhihui Sun; Shaoxiong Li; Yanbin Hong; Rajeev K. Varshney; Lu Huang; Runfeng Wang; Qianxia Yu; et al. (Food Chemistry, 2026)

Nanotechnology driven paradigms for sustainable agriculture: A holistic assessment of efficacy, mechanisms, and environmental footprint - Wajid Saeed; Samavia Mubeen; Sana Basharat; Qiqi Peng; Aliya Ayaz; Enerand Mackon; Muhammad Umer; Furkhanda Kalsoom; Muhammad Waseem; Yun li; Pingwu Liu (European Journal of Agronomy, 2026)

Quantifying provincial contributions to carbon intensity reduction in China’s construction industry: ML-assisted analysis via an integrated LMDI-ANCOVA framework - Yunxiao Yuan; Marko Lovrić; Han Zhang; Muhammad Umer; Xiaoyu Yang; Yu Xu; Mei Qu (Energy and Buildings, 2026)

Multi-sensor deep learning approach for landslide susceptibility mapping under climate and anthropogenic pressures - Xiuping Zhang; Xulong Duan; Umer Khalil; Muhammad Ali Muhammadi; Hela Elmannai; Abeer D. Algarni; Dmitry E. Kucher (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Engineering hybrid hydrogels from sticker–spacer peptide and molybdenum disulfide (MoS2) for advanced antimicrobial therapy - Muhammad Younis; Farhat Rafiq; Shuo Jin; Mussarat Tasleem; Muhammad Saleem; Yongchang Tian; Li Chen; Mohammad Aslam; Dalaver H. Anjum; Jabir Ubaid; Rehan Umer; Xiaofei Chen; et al. (Chemical Engineering Journal, 2026)

Bridging Lab to Land: Field Validation of Acinetobacter schindleri SR-5–1 for Nutrient Acquisition and Oxidative Stress Mitigation in Wastewater-Irrigated Pea (Pisum sativum L.) Plants - Sherjeel Hashmat; Muhammad Arslan Ashraf; Muhammad Tariq Javed; Umer Farooq; Mobeen Umer (Water, Air, & Soil Pollution, 2026)

Advances in Coated Urea Technology: Toward Climate-responsive, Microbiome-friendly, and Site-specific Nitrogen Management - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Shazia Hanif; Aqsa Andleeb Sial; Muhammad Umair Hassan; Tahani A.Y. Asseri; Rehab O. Elnour (Journal of Soil Science and Plant Nutrition, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

The empirical study on the impact of transportation sector, electricity production, and foreign direct investment on carbon emissions in China - Muhammad Umer Aslam; Jiani Wu; Muhammad Kamran Aslam (Environment, Development and Sustainability, 2026)

Precision Agriculture Through Green Nanoparticles: Mechanistic Insights into Nutrient Delivery and Enzyme-Targeted Pest Control with Emerging Computational Perspectives - Muhammad Irfan; Hira Altaf; Mishal Naveed; Nadia Zeeshan; Umer Rashid; Amber Afroz (Journal of Soil Science and Plant Nutrition, 2026)

Characterization of stable grain protein content loci on chromosome 6D without adverse effect on yield traits in bread wheat - Hang Liu; Chao Wang; Jiating Chen; Huaping Tang; Tongzhu Wang; Md Nahibuzzaman Lohani; Hafiz Muhammad Faisal Umer; Muhammad Junaid Jalil; Haopeng Zhang; Xia Yang; Qiang Xu; Jian Ma; et al. (Theoretical and Applied Genetics, 2026)

Unraveling the synergistic effects of Bacillus cereus and different concentrations of silicon nanoparticles on wheat under rain-fed conditions of Pakistan - Muhammad Umer; Kahkashan Perveen; Faheema Khan; Jayanthi Barasarathi; Naeem Khan; Nageen Bostan; Summiya Faisal; Zainab Asif; Noshin Ilyas (Environmental Geochemistry and Health, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Performance Investigation of ML Algorithms for Potato Blight Classification: The Role of Hyperparameter Tuning - Sadia Saeed; Hafiz Zia Ur Rehman; Muhammad Ureed Hussain; Muhammad Umer Khan; Muhammad Tallal Saeed (Journal of Crop Health, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Multifunctional Curcumin Nanoparticles: Oncolytic, Radical Scavenging, Regenerative, Hepatoprotective, and Bactericidal Effects - Huzaifa Hanif; Shahzad Hussain; Umer Rashid; Tafail Akbar Mughal; Muhammad Naeem Ahmad; Muhammad Waseem (Cell Biochemistry and Biophysics, 2026)

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

Examining the Role of Corporate Digital Orientation in Fostering Firms’ Green Innovation: Evidence from Chinese Firm Life Cycle Stages - Murtaza Hussain; Shaohua Yang; Umer Sahil Maqsood; Muhammad Waleed Younas; R. M. Ammar Zahid (Journal of Environmental Management, 2026)

Antimicrobial Peptides as Next-Generation Disinfectants: Tackling Biocide and Antimicrobial Resistance in Hospital Hygiene – A Narrative Review - Muhammad Umer Asghar; Noor Ul Ain; Muhammad Tariq; Arsalan Haseeb Zaidi (Probiotics and Antimicrobial Proteins, 2026)

Biochemical signatures shaping tissue culture success in maize inbred lines - Rimsha Akhtar; Kauser A. Malik; Umer Zeeshan Ijaz; Asma Maqbool; Zohab Asif; Muhammad Irfan (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Trichoderma Enhance Soil Properties in Fusarium Infested Soil and Increase Mineral Nutrients of Chickpea Grains: Findings from Field Experiments - Safeer Akbar Chohan; Muhammad Akbar; Muhammad Asad Farooq; Nasim Ahmad Yasin; Umer Iqbal; Tayyaba Khalil (Journal of Soil Science and Plant Nutrition, 2026)

Coated Urea Improves Productivity and Nitrogen Use Efficiency in Wheat - Muhammad Talha Aslam; Imran Khan; Muhammad Umer Chattha; Ghulam Murtaza (Journal of Soil Science and Plant Nutrition, 2026)

Brassinosteroids: Key Players to Improve Drought Tolerance and Crop Productivity - Muhammad Inzamam-UL-Haq; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Sezai Ercişli; Uthman Balgith Algopishi; Fatima M. Abbas; Mohamed Hashem; Muhammad Mahmood Iqbal; Muhammad Umair Hassan (International Journal of Plant Production, 2026)

Sulfur-Coated Urea Improves Rice productivity, Nitrogen Use Efficiency, and Soil Nitrogen Dynamics Under Alternate Wetting and Drying System - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Muhammad Bilal Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Umair Hassan; Uthman Balgith Algopishi; Mohamed Hashem; Sezai Ercişli (International Journal of Plant Production, 2026)

Modelling adoption of camera-based safety monitoring systems in construction: an extended technology acceptance model approach using PLS-SEM - Nawal Manzoor; Hilal Khan; Muhammad Usman Hassan; Khursheed Ahmed; Muhammad Umer Zubair (Innovative Infrastructure Solutions, 2026)

Calocybe barangensis sp. nov (Lyophyllaceae), from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Dege Zheng; Umer Rehman; Muhammad Asif; Syed Mohammad Tauseeq Ali Shah; Dong‐Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this study, we report a new taxon, Calocybe barangensis , from Barang, Bajaur District, Khyber Pakhtunkhwa, Pakistan. The species was described as new to science using molecular phylogenetic analysis of combined ITS and LSU datasets, as well as comparisons of its macro‐ and micromorphological characteristics with those of similar taxa. The new species forms a separate clade in the phylogenetic tree and differs in having small basidiomata with dark yellowish‐brown spores and large, globose to subglobose basidiospores (5.9–7.2 × 4.7–5.6 μm). A full description, illustrations, and phylogenetic analysis results of the new species are provided.

Overcoming the Challenges of Viscous Simulated Fed State Media with a Computerized Numerical Control Tablet Disintegration and Dissolution Tester - Valentin Stahl; Muhammad Farooq Umer; Jozef Al-Gousous; Thomas Nawroth; Wei-Jhe Sun; Fang Wu; Wenlei Jiang; Zongming Gao; Peter Langguth (AAPS PharmSciTech, 2026)

Mechanistic insights into PVC microplastic adsorption on montmorillonite: A first-principles approach toward pollution control - Hafiz Muhammad Umer Aslam; Achintya Bezbaruah; Dmitri Kilin (Environmental Science and Pollution Research, 2026)
Plastic pollution has emerged as a pervasive environmental threat, with polyvinyl chloride (PVC) being a persistent polymer that can degrade into smaller fragments. These particles contaminate aquatic environments, accumulate in biota, and pose serious ecological and health risks. This study used computational methods to investigate the adsorption of vinyl chloride (VC), a PVC oligomer, onto montmorillonite (MMT). Vienna Ab initio Simulation Package was used to perform Density Functional Theory calculations. The interaction between VC and MMT was assessed through binding energy, density of states (DOS), projected DOS, and charge analysis. A negative binding energy (− 0.62 eV) confirmed favorable adsorption. The reduced HOMO–LUMO gap in the VC–MMT hybrid indicated electronic interactions. The orbital-resolved projected density of states (PDOS) showed overlap between the O 2p orbitals of MMT and the H 1 s orbitals of VC. Bader charge analysis revealed negligible charge transfer to the VC molecule upon adsorption, while charge density difference showed localized electron redistribution at the VC–MMT interface. These results indicate a noncovalent interaction without the formation of shared charge density, consistent with polarization-driven physisorption. Molecular dynamics simulations supported these interactions, showing that the VC molecule remained associated with the MMT surface through noncovalent forces. Root mean square deviation (RMSD) confirmed that the VC–MMT structure remained stable throughout the simulation, while the interaction energy exhibited stable fluctuations over time. These findings suggest that MMT holds potential as an effective sink for PVC microplastics through stable, non-covalent surface retention, thereby reducing their dispersion in environmental matrices. Graphical Abstract

A novel solution pollination in orchards - Feiran Wang; Lixing Xie; Yao Zhou; Jiangrui Dai; Likai Feng; Guoli Zhang; Zongcai Zhu; Yancun Zhao; Baolian Tian; Xiuli Shi; Donglan Lv; Muhammad Imran; et al. (Journal of Cleaner Production, 2026)

Enhancing Lodging Resistance in Rapeseed Strategies for Sustainable Agriculture and Yield Improvement - Shahid Ullah Khan; Umer Mahmood; Muhammad Sirab Khan; Minchao Qian; Shengting Li; Osama Alam; Yonghai Fan; Hui Wang; Wei Chang; Hameed Gul; Shah Fahad; Kun Lu (Journal of Plant Growth Regulation, 2026)

Management of canola aphids (Hemiptera: Aphididae) using potassium silicate (K2SiO3) in integration with Chrysoperla carnea Stephens - Dilawar Abbas; Umer Liaqat; Habib Ali; Tehniyat Fatima; Ammara Riaz; Inzamam Ul Haq; Zahid Mahmood Sarwar; Muhammad Abaid Ullah; Muhammad Adeel Ghafar; Kamran Haider; Muhammad Lubaid Khalid; Modhi O. Alotaibi; et al. (Journal of Plant Diseases and Protection, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Biochar: Acinetobacter driven rhizoremediation of arsenic contaminated soil - Maria Hameed; Muhammad Umer; Maimona Saeed; Nageen Bostan; Noshin Ilyas (Environmental Geochemistry and Health, 2026)

Optimizing bioenergy biofuel harvest: a comparative analysis of stepwise and integrated methods for economic and environmental sustainability - Muhammad Umer Arshad; David Archer; Nictor Namoi; Daniel Wasonga; Chunhwa Jang; Tim Rooney; DoKyoung Lee (Bioresource Technology, 2026)

Facile synthesis of novel MgO/NaCl nanosheets for extremely high Ni(II) adsorption from aqueous solutions: Experimental, mathematical, DFT and Box-Behnken design analysis - Khurram Shehzad; Aqdas Shehzad; Mukhtar Ahmad; Hongbo Ou; Suci Meng; Muhammad Aamir Aslam; Umer Farooq; Yan Wang; Min Chen; Yu Gan; Yuanguo Xu (Journal of Environmental Chemical Engineering, 2025)

Bridging the gap: Advancing behavioral economics and climate change research in developing countries - Hamza Umer; Muhammad Salar Khan (Energy and Climate Change, 2025)

Catalyst driven optimization of cogasification and economic evaluation for enriched hydrogen syngas production from lignocellulosic waste toward biorefinery applications - Suhaib Umer Ilyas; Muddasser Inayat; Muhammad Shahbaz; Shaharin A. Sulaiman; Noor A. Merdad; Aymn Abdulrahman (Biomass and Bioenergy, 2025)

Correction: Citrulline enhances salinity tolerance via photosynthesis, redox balance, osmotic and hormonal regulation, and nutrient assimilation in sunflower (Helianthus annuus L.) - Umer Farooq; Muhammad Arslan Ashraf; Rizwan Rasheed (Physiology and Molecular Biology of Plants, 2025)

Unveiling the spectrum of vancomycin resistance in Staphylococcus aureus from Hospital-acquired urinary tract infections (HA-UTI) in cardiac patients - Muhammad Umer Asghar; Muhammad Tariq; Arsalan Haseeb Zaidi; Kabeer Haneef; Aisha Asghar; Noor Ul Ain (Molecular Biology Reports, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Evaluation of Agronomic Traits and Bioactive Compounds in Five Mentha Species Under Soil-Based and Hydroponic System - Muhammad Azam Khan; Ismara Naseem; Muhammad Tahir Akram; Umer Habib; Rashid Mehmood Rana (Journal of Soil Science and Plant Nutrition, 2025)

Integrative genomics and genetics from evolutionary insights to precision breeding in peanuts (Arachis Hypogaea L.) - Muhammad Jawad Umer; Lu Huang; Hao Liu; Raufa Batool; Haifen Li; Shaoxiong Li; Yanbin Hong; Runfeng Wang; Qianxia Yu; Qing Lu; Rajeev K. Varshney; Xiaoping Chen (Functional & Integrative Genomics, 2025)

Effect of citrulline seed priming on growth, photosynthesis, redox equilibrium, secondary metabolic enzymes, metal sequestration and nutrient acquisition in sunflower (Helianthus annuus L.) under chromium toxicity - Umer Farooq; Muhammad Arslan Ashraf; Muhammad Iqbal; Rizwan Rasheed (BioMetals, 2025)

Paleoenvironmental and organic facies analysis of potential hydrocarbon source rocks in Surghar Range, Kohat Plateau - Arif Nazir; Fraz Khalid; Saeed Abbas; Muhammad Deen; Munawar Iqbal; Umer Younas; Muhammad Iftikhar Khan; Rab Nawaz (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Incorporating dynamic crop area in hydrological model to address interannual variability in water withdrawal and implication of sustainable water management - Muhammad Umer; Naota Hanasaki; Saritha Padiyedath Gopalan; Zeshan Ali; Taikan Oki (Journal of Hydrology, 2025)

Digital pathways to sustainability: The role of Europe-Central Asia region's digitalization, trade, and geography maximizing sustainable development in China - Umer Shahzad; Said Muhammad (Journal of Environmental Management, 2025)

Liquid biopsy in breast cancer: clinical implications of ctDNA and CTCs in diagnosis, treatment and monitoring - Muhammad Umer Khan; Arooj Khawar; Muhammad Ikram Ullah; Muhammad Adnan Shan; Luca Falzone; Massimo Libra; Graziana Spoto; Javad Sharifi-Rad; Daniela Calina (Molecular and Cellular Biochemistry, 2025)

Towards greening smart cities: Navigating net zero carbon in construction by 2050 through sustainable practices, innovation climate, and management support - Muhammad Javid Nawaz; Aymen Sajjad; Abdul Haseeb Tahir; Muhammad Adnan; Muhammad Umer; Huaming Song (Sustainable Cities and Society, 2025)

Xanthan gum coating delays ripening of harvested mango (Mangifera indica L.) fruit by suppressing chlorophyll catabolism and cell wall polysaccharides degradation - Maimona Qasim; Sajid Ali; Hafiz Umer Javed; Safina Naz; Ahmad Sattar Khan; Muhammad Hassan; Rana Naveed Ur Rehman (Postharvest Biology and Technology, 2025)

Genome-wide identification, characterization and expression analysis of CsC3H gene family in cucumber (Cucumis sativus L) under various abiotic stresses - Saleem Uddin; Sadia Gull; Hafiz Athar Hussain; Umer Mahmood; Muhammad Qasim; Farah Kamal; Abdel-Rhman Z. Gaafar; Saltanat Aghayeva; Rashid Iqbal; Xiaohong Yang (Plant Science, 2025)

Synergistic effects of Ti3C2 MXene and ZIF-8 for efficient photocatalytic degradation of tetracycline in wastewater - Saeed Sajjadi; Michal Žitňan; Muhammad Umer Iqbal; Michal Machovský; Pedro Núñez; Dana Dvoranová; Dušan Galusek; Róbert Klement; Jose J. Velázquez (Journal of Environmental Chemical Engineering, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Climate Change Impacts on Fruit Crops and Mechanisms of Stress-Induced Disease Dynamics for Resilience Strategies - Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Dinaphthodiospyrol H: a natural α-glucosidase inhibibitor extracted from Diospyros kaki L.f - Abdur Rauf; Taghrid S. AlOmar; Umer Rashid; Zubair Ahmad; Sofia Kanwal; Najla Almasoud; Naveed Muhammad; Margrate Anyanwu; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2025)

Nature-inspired bio-composites for phosphate sequestration and recovery: Green synthesis, mechanistic insights, and multi-stage optimization - Hafiz Muhammad Umer Aslam; Saurabh Singh; Mohiuddin Quadir; Achintya N. Bezbaruah (Science of The Total Environment, 2025)

Circular RNAs: Diversity, formation, functions, and identification mechanism with a focus on endogenous circular RNAs - Muhammad Umer; Naureen Anwar; Mustansar Mubeen; Yasir Iftikhar; Manoj Kumar Solanki; Muhammad Ahmad Zeshan; Khalid M. Alsyaad; Yun Li; Pingwu Liu (Physiological and Molecular Plant Pathology, 2025)

A metagenomics-based approach to understanding the transmission of healthcare-associated antimicrobial resistance in Pakistan - Muhammad Umer Asghar; Yuting Zhai; Ting Liu; Peixin Fan; Noor Ul Ain; Arsalan Haseeb Zaidi; Muhammad Tariq; Raul C. Mainar-Jaime; Kwangcheol C. Jeong (Journal of Hazardous Materials, 2025)

Phycocyanin as a sustainable future resource: A review on recent advancements, fundamental challenges, opportunities and applications - Haider Ali; Rashid Iftikhar; Muhammad Ali Inam; Muhammad Umer Abbas; Sahar Saleem; Faras Ahmad Shahbaz; Humayun Nadeem; Aleena Tahir; M. Momin (Bioresource Technology Reports, 2025)

Heavy metals removal and reduction of heavy metal phytotoxicity by Arthrobacter, Bacillus, and Pseudomonas strains harboring genes encoding metal resistance - Muhammad Tahir; Muhammad Nasir; Tahir Naqqash; Muhammad Shahid; Abu Bakr Umer Farooq; Muhammad Akram; Muhammad Arshad; Muhammad Kamran; Urooj Khan (Biocatalysis and Agricultural Biotechnology, 2025)

Correction: Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Multivariate and Association Analyses of Various Seed Yield Contributing Traits Divulge Genetic Diversity Among Pisum sativum L. Genotypes - Noshi Parveen; Shamim Umer; Changwei Tan; Abdul Jabbar; Bilqees Kanwal; Imran Haider; Waqas Raza; Anwer Usma; Aqib Mahmood; Muhammad Bilawal Junaid; Salman Haidar Abbasi; Alanoud T. Alfagham; et al. (Plant Molecular Biology Reporter, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Machine learning assisted predictive urban digital twin for intelligent monitoring of air quality index for smart city environment - Khazina Naveed; Tariq Umer; Aamer Bilal Asghar; Muhammad Aslam; Krzysztof Ejsmont; Ahmed Sayed Mohammed Metwally; Kien Nguyen Thanh (Environmental Modelling & Software, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Rapid synthesis of charged covalent organic framework for sustainable reverse osmosis membranes - Umar H. Nuhu; Niaz Ali Khan; Ijaz Hussain; Mengying Long; Billel Salhi; Nadeem Baig; Ismail Abdulazeez; Khan Alam; Sikandar Khan; Muhammad Usman; Umer Zahid; Isam H. Aljundi (Desalination, 2025)

A host availability-driven model for predicting the distribution of Red Palm Weevil in China - Umer Hayat; Muhammad Hammad Ahmad; Waqar Sattar; Ziying Zhu (Crop Protection, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

Optimising polyoxometalate catalysed hydrogen generation from poultry litter-biomass electrolysis through response surface methodology - Muhammad Umer; Caterina Brandoni; Svetlana Tretsiakova; Neil Hewitt; Patrick Dunlop; Ye Huang (Biomass and Bioenergy, 2025)

Interesterification of waste cooking oil via microwave irradiation for glycerol-free biodiesel production - Muhammad Umer Qadeer; Muhammad Ayoub; Muhammad Hamza Nazir; Muhammad Asad Javed; Zulqarnain; Imtisal Zahid; Mariam Ameen; Farooq Sher; Alhassan Ibrahim (Biomass and Bioenergy, 2025)

Citrulline enhances salinity tolerance via photosynthesis, redox balance, osmotic and hormonal regulation, and nutrient assimilation in sunflower (Helianthus annuus L.) - Umer Farooq; Muhammad Arslan Ashraf; Rizwan Rasheed (Physiology and Molecular Biology of Plants, 2025)

Mitigating the Greenhouse Gases Intensity and Improving Fine Rice Productivity with Coated Urea Fertilizers in Semi-Arid Conditions - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Hafiz Abdul Wahab; Faisal Nadeem; Rikza Awan; Uthman Balgith Algopishi; Mohamed Hashem; Muhammad Umair Hassan (Journal of Soil Science and Plant Nutrition, 2025)

Physicochemical, Enzymatic, and Microbial Responses to Phosphofructokinase Overexpressing Transgenic Potato Cultivation: A Pot Experiment - Muhammad Junaid Sadiq Gill; Umer Ali; Aqib Hassan Ali Khan; Ismat Nawaz; Tayyab Ashfaq Butt; Cyrus Raza Mirza; Ameena Iqbal; Arfan Ali; Faiz Ur Rahman; Sohail Yousaf; Mazhar Iqbal (American Journal of Potato Research, 2025)

Development and Optimization of Stimuli-Responsive Fenugreek/Carrageenan-Co-poly (Methacrylate) Hydrogel Matrices for Controlled Delivery of 5-Fluorouracil - Muhammad Arslan; Muhammad Umer Ashraf; Ayman M. Al-Qaaneh; Aysha Aslam; Asif Mahmood; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Milad A. Mezher; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Effects of neem leaf extract on physiochemical traits and antioxidant activity of peach fruit during storage - Jianhui Li; Muhammad Hanif; Muhammad Azam; Muhammad Arslan Khan; Muhammad Ali Umer; Beenish Chaudhary; Imtiaz Hussain; Tariq Aziz Khan; Shoaib ur Rehman; Muhammad Awais; Riadh Ilahy; Hongru Liu; et al. (Journal of Stored Products Research, 2025)

Carrageenan based edible coating modulates oxidative stress and delays cell wall polysaccharides disassembly in harvested grapefruit - Sajid Ali; Sidra Riaz; Hafiz Umer Javed; Ahmad Sattar Khan; Maratab Ali; Safina Naz; Hasan Sardar; Muhammad Shahzad Saleem (Journal of Stored Products Research, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Exploring the potential of a pH-sensitive hydrogel sponge: interpenetrating network of tragacanth and pectin for controlled delivery of levosulpiride - Muhammad Umer Ashraf; Muhammad Awais Iqbal; Kashif Barkat; Irfan Anjum; Muhammad Naveed Mushtaq; Rabia Gul; Muhammad Aamir; Samir Ibenmoussa; Ahmad Mohammad Salamatullah; Mohammed Bourhia; Gamal A. Shazly; Gezahign Fentahun Wondmie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Digital and geographical mobility: correlating technological bilateral trade impact on sustainable trade development between China and East Asia - Umer Shahzad; Changhong Miao; Said Muhammad (Environment, Development and Sustainability, 2025)

Chemical profile changes in Peanut seeds infected with aspergillus flavus via widely targeted metabolomics - Yueni Zhou; Mengyun Xu; Muhammad J. Umer; Runfeng Wang; Yuan Xiao; Zihao Zheng; Dongxin Huai; Shaoxiong Li; Qing Lu; Yanbin Hong; Xiaoping Chen; Hao Liu (Food Chemistry, 2025)

Diatom derived hollow 3D Frame as a synergetic support for millerite nanoparticles: A unique hydrogen evolution electrocatalyst and its mechanistic insights - Atanu Panda; Younghu Son; Muhammad Umer; Geunsik Lee; Mani Balamurugan; Jihyun Lee; Wooyul Kim; Reddicherla Umapathi; EA Lohith; K. Keerthi; Ki Tae Nam; Radek Zboril; et al. (Chemical Engineering Journal, 2025)

Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2025)

Valorization of recycled steel wires from end-of-life tires as an alternative fiber reinforcement in geopolymer concrete to foster circularity: a review - Muhammad Umer; Junaid Ahmad; Hammad Anis Khan; Rao Arsalan Khushnood (European Journal of Environmental and Civil Engineering, 2025)

Morphological profiling and DNA barcoding revealed genetic diversity and phylogeny of Mentha species cultivated in Pakistan - Ismara Naseem; Muhammad Azam Khan; Umer Habib; Rashid Mehmood Rana; Muhammad Qasim; Mona S. Alwahibi; Rizwana Khanum; Muhammad Shafiq; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Exploring the therapeutic potential of Ixora extract: a comprehensive review of mediated studies - Rabiyah Nadeem; Muhammad Imran; Zohaib Saeed; Muhammad Pervaiz; Umer Younas (Advances in Traditional Medicine, 2025)

Retraction notice to “A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites” [Fuel 336 (2023) 126930] - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2025)

Retraction notice to Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review [FUEL][340][2023][127399] - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2025)

Modeling and analysis of a carbon capturing system in forest plantations engineering with Mittag–Leffler positive invariant and global Mittag–Leffler properties - Muhammad Umer Saleem; Muhammad Farman; Rabia Sarwar; Parvaiz Ahmad Naik; Perwasha Abbass; Evren Hincal; Zhengxin Huang (Modeling Earth Systems and Environment, 2025)

RbcLa marker based identification and phylogenetic analysis of Kasuri methi (Trigonella foenum-graecum L.): a native plant of Kasur district of Punjab (Pakistan) - Bin Yameen; Wasim Abbas; Muhammad Umer Farooq Awan; Aisha Tahir; Sohaib Mohammad; Muhammad Shoib (Genetic Resources and Crop Evolution, 2025)

Evaluating the safety and effectiveness of tolvaptan in patients with heart failure and renal impairment: a systematic review and meta-analysis - Aashish Kumar; Umer Iqbal; Shafin Bin Amin; Syed Ali Arsal; Syed Muhammad Sinaan Ali; Muhammad Ashir Shafique; Muhammad Saad Shahid; Aimen Naz; Emediong Santhus Asuka (European Journal of Clinical Pharmacology, 2025)

Food-derived phytochemicals from functional food (Allium sativum) as VEGF-R1 inhibitors: A novel approach for triple-negative breast cancer therapy - Abia Mahboob; Rashida Bashir; Ahmad Adnan; Muhammad Umer Khan; Umair Khurshid; Anjum Khursheed; Mhdia Elhadi Osman; Halima Mustafa Elagib; Nuha M.E. Agabna (Food Bioscience, 2025)

Two-dimensional MXene based innovative electrode materials for supercapacitors: Recent advances and prospects - Salamat Ali; Muhammad Ahsan Farooq Qaisar; Muhammad Sufyan Javed; Khalid Umer; Saleh S. Alarfaji; Muhammad Mateen; Muhammad Chhattal; Shafqat Ali; Anand Parkash; Tensangmu Lama Tamang; Jing Qi (Fuel, 2024)

Prevalence and associated risk factors of Brucella abortus and Brucella melitensis in humans and cattle populations: A comprehensive study - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Molecular prevalence, phylogenetic analysis, and PCR-based detection of Brucella melitensis in humans and cattle in Southern Khyber Pakhtunkhwa, Pakistan - Ihsan Ullah; Shumaila Naz; Umer Sadique Khattak; Muhammad Saeed; Noor ul Akbar; Sania Rauf (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Deciphering the differential expression patterns of yield-related negative regulators in hexaploid wheat cultivars and hybrids at different growth stages - Muhammad Jawad Akbar Awan; Muhammad Awais Farooq; Rubab Zahra Naqvi; Umer Karamat; Sayyad Ali Raza Bukhari; Muhammad Abu Bakar Waqas; Muhammad Arslan Mahmood; Muhammad Ismail Buzdar; Awais Rasheed; Imran Amin; Nasir A. Saeed; Shahid Mansoor (Molecular Biology Reports, 2024)

Biological role and regulation of circular RNA as an emerging biomarker and potential therapeutic target for cancer - Ayman Saleem; Muhammad Umer Khan; Tazeen Zahid; Iqra Khurram; Muhammad Usman Ghani; Inam Ullah; Rakhtasha Munir; Daniela Calina; Javad Sharifi-Rad (Molecular Biology Reports, 2024)

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

Removal of chlorpyrifos from aqueous medium using Ca-CuO@clay nanoflakes coated with deep eutectic solvent - Abdullah Zia; Umer Younas; Zahid Ali; Rabia Nazir; Faisal Ali; Aemin Irfan; Muhammad Pervaiz (Environmental Monitoring and Assessment, 2024)

Sustainable development goals and green human resource management: A comprehensive review of environmental performance - Abdul Haseeb Tahir; Muhammad Umer; Shazia Nauman; Kashif Abbass; Huaming Song (Journal of Environmental Management, 2024)

Detection of Mobile and Immobile Solute Transport and Their Residence Time in Saturated Low and High Permeability Soil Layers - Muhammad Zaheer; Ehsan Ul Haq; Ning Huang; Ahmed Amara Konaté; Ghulam Mujtaba Shah; Raja Umer Sajjad; Saad Ahmed Mashwani (Water, Air, & Soil Pollution, 2024)

Retraction Note: Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Maria Khalil; Muhammad Asif Hanif; Umer Rashid; Junaid Ahmad; Ali Alsalme; Toshiki Tsubota (Environmental Science and Pollution Research, 2024)

Ensemble transfer learning using MaizeSet: A dataset for weed and maize crop recognition at different growth stages - Zeynep Dilan Daşkın; Muhammad Shahab Alam; Muhammad Umer Khan (Crop Protection, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

MoS2@Ti3C2T Heterostructure: A new negative electrode material for Li-Ion hybrid supercapacitors - Salamat Ali; Muhammad Sufyan Javed; Khalid Umer; Jiatai Wang; Yujun Fu; Shunlian Kong; Shaukat Khan; Awais Ahmad; Anand Parkash; Munirah D. Albaqami; Annu; Jing Qi; et al. (Chemical Engineering Journal, 2024)

Production and optimization of biofuels from locally isolated algal biomass: Strategies for circular economy integration - Muhammad Uzair Javed; Iqra Nazeer; Hamid Mukhtar; Umer Rashid; Maria J. Sabater; Fahad A. Alharthi (Biocatalysis and Agricultural Biotechnology, 2024)

Flaxseed mucilage—a green additive for the enhancement of water-based mud system characteristics - Faiza Kanwal; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney; Muhammad Ovais Tariq; Leena Hasan Ahmed; Umer Ahmed Khan; Aashan Sheikh; Muhammad Salman (Arabian Journal of Geosciences, 2024)

Flavonoids from Pistacia chinensis subsp. integerrima with leishmanicidal activity: computational and experimental evidence - Abdur Rauf; Umer Rashid; Abdullah Muhammad Shbeer; Mohammed Al-Ghorbani; Naveed Muhammad; Anees Ahmed Khalil; Humaira Naz; Rohit Sharma; Giovanni Ribaudo (Natural Product Research, 2024)

Seed Priming with Taurine Debilitates Copper Phytotoxic Effects by Maintaining Redox Balance, Ions Homeostasis and Photosynthetic Efficiency in Canola (Brassica napus L.) - Sadia Zafar; Rizwan Rasheed; Umer Farooq; Muhammad Arslan Ashraf; Shafaqat Ali; Mohammed Ali Alshehri; Khalid A. Al-Ghanim; Pallab K. Sarker (Journal of Soil Science and Plant Nutrition, 2024)

Metrics for Sustainability and Circular Economy Practices in Context to Modern Manufacturing Environment - Mohd Bilal Naim Shaikh; Mohammed Ali; Umer Masood Chaudry; Muhammad Kashif Khan (Circular Economy and Sustainability, 2024)

Waste Palm Leaves-Based Hydrochar Support Catalytic Esterification of Palm Fatty Acid Distillate - Muhammad Aliyu; Umer Rashid; Wan Azlina Wan Ab Karim Ghani; Mohamad Amran Mohd Salleh; Balkis Hazmi; Fahad A. Alharthi; Elsa Antunes; Jianglong Yu (BioEnergy Research, 2024)

Drivers of municipal water security and vulnerability in Pakistan: A case study of Mardan, Khyber Pakhtunkhwa - Kamran; Junaid Aziz Khan; Fasiha Safdar; Umer Khayyam; Iftikhar Hussain Adil; Abdul Waheed; Muhammad Fahim Khokhar (Groundwater for Sustainable Development, 2024)

Efficient production of biodiesel from palm fatty acid distillate using a novel hydrochar-based solid acid catalyst derived from palm leaf waste - Muhammad Aliyu; Bryan R. Moser; Fahad A. Alharthi; Umer Rashid (Process Safety and Environmental Protection, 2024)

Characterization of the future northeast monsoon rainfall based on the clustered climate zone under CMIP6 in Peninsular Malaysia - Zulfaqar Sa'adi; Nor Eliza Alias; Zulkifli Yusop; Mohammed Magdy Hamed; Prabhakar Shukla; Mohamad Rajab Houmsi; Nur Athirah Mohamad; Mohammed Sanusi Shiru; Nurzalikha Sa'adi; Mohd Khairul Idlan Muhammad; Zafar Iqbal; Umer Jeelanie Banday (Atmospheric Research, 2024)

Improving urban road infrastructure analysis and design using an integrated BIM-GIS and traffic microsimulation framework - Mohammad Sohaib; Aaqib Najeeb; Muhammad Umair; Muhammad Arsalan Khan; Muhammad Umer Zubair; Zulqarnain Jehan; Afaq Khattak (Innovative Infrastructure Solutions, 2024)

Assessment of hydrochemical characteristics, health risks and quality of groundwater for drinking and irrigation purposes in a mountainous region of Pakistan - Waqar Azeem Jadoon; Muhammad Zaheer; Abdul Tariq; Raja Umer Sajjad; Memet Varol (Environmental Science and Pollution Research, 2024)
Renowned for its agriculture, livestock, and mining, Zhob district, Pakistan, faces the urgent problem of declining groundwater quality due to natural and human-induced factors. This deterioration poses significant challenges for residents who rely on groundwater for drinking, domestic, and irrigation purposes. Therefore, this novel study aimed to carry out a comprehensive assessment of groundwater quality in Zhob district, considering various aspects such as hydrochemical characteristics, human health risks, and suitability for drinking and irrigation purposes. While previous studies may have focused on one or a few of these aspects, this study integrates multiple analyses to provide a holistic understanding of the groundwater quality situation in the region. Additionally, the study applies a range of common hydrochemical analysis methods (acid–base titration, flame atomic absorption spectrometry, and ion chromatography), drinking water quality index (WQI), irrigation indices, and health risk assessment models, using 19 water quality parameters. This multi-method approach enhances the robustness and accuracy of the assessment, providing valuable insights for decision-makers and stakeholders. The results revealed that means of the majority of water quality parameters, such as pH (7.64), electrical conductivity (830.13 μScm –1 ), total dissolved solids (562.83 mgL –1 ), as well as various anions, and cations, were in line with drinking water norms. However, the water quality index (WQI) predominantly indicated poor drinking water quality (range = 51–75) at 50% sites, followed by good quality (range = 26–50) at 37% of the sites, with 10% of the sites exhibiting very poor quality (range = 76–100). For irrigation purposes, indices such as sodium percent (mean = 31.37%), sodium adsorption ratio (mean = 0.98 meqL –1 ), residual sodium carbonate (– 3.15 meqL –1 ), Kelley’s index (mean = 0.49), and permeability (mean = 49.11%) indicated suitability without immediate treatment. However, the magnesium hazard (mean = 46.11%) and potential salinity (mean = 3.93) demonstrated that prolonged application of groundwater for irrigation needs soil management to avoid soil compaction and salinity. Water samples exhibit characteristics of medium salinity and low alkalinity (C2S1) as well as high salinity and low alkalinity (C3S1) categories. The Gibbs diagram results revealed that rock weathering, including silicate weathering and cation exchange, is the primary factor governing the hydrochemistry of groundwater. The hydrochemical composition is dominated by mixed Ca–Mg–Cl, followed by Na–Cl and Mg–Cl types. Furthermore, the human health risk assessment highlighted that fluoride (F – ) posed a higher risk compared with nitrate (NO 3 – ). Additionally, ingestion was found to pose a higher risk to health compared to dermal contact, with children being particularly vulnerable. The average hazard index (HI) for children was 1.24, surpassing the allowable limit of 1, indicating detrimental health effects on this subpopulation. Conversely, average HI values for adult females (0.59) and adult males (0.44) were within safe levels, suggesting minimal concerns for these demographic groups. Overall, the study’s interdisciplinary approach and depth of analysis make a significant contribution to understanding groundwater quality dynamics and associated risks in Zhob district, potentially informing future management and mitigation strategies.

Development and validation of an indirect ELISA for the serodiagnosis of contagious caprine pleuropneumonia in goats - Hayatullah Khan; Farhan Anwar Khan; Umer Sadique; Ijaz Ahmad; Muhammad Saeed; Faisal Ahmad; Faiz Ur Rehman; Hanif Ur Rahman (Small Ruminant Research, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

Pervasive influence of heavy metals on metabolic pathways is potentially relieved by hesperidin to enhance the phytoremediation efficiency of Bassia scoparia - Mazhar Hussain; Arslan Hafeez; Muhammad Rizwan; Rizwan Rasheed; Mahmoud F. Seleiman; Muhammad Arslan Ashraf; Shafaqat Ali; Umer Farooq; Muhammad Nafees (Environmental Science and Pollution Research, 2024)

Innovative valorization of biomass waste-derived sodium silicate for geopolymer concrete synthesis: Sustainability assessment and circular economy potential - Muhammad Umer; Junaid Ahmad; Hina Mukhtar (Journal of Cleaner Production, 2024)

Green synthesis of ZnO nanocubes from Ceropegia omissa H. Huber extract for photocatalytic degradation of bisphenol An under visible light to mitigate water pollution - Awais Ahmad; Muhammad Ramzan Khawar; Ikram Ahmad; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Umer Younas; Arif Nazir; Dongwhi Choi; Abdulnasser M. Karami (Environmental Research, 2024)

High strength rubberized porous concrete for sustainable pavements: Engineering properties and life cycle assessment - Musa Ajmal Khan; Junaid Ahmad; Hammad Anis Khan; Muhammad Umer (Journal of Cleaner Production, 2024)

Evaluation of soil texture classification from orthodox interpolation and machine learning techniques - Lei Feng; Umer Khalil; Bilal Aslam; Bushra Ghaffar; Aqil Tariq; Ahsan Jamil; Muhammad Farhan; Muhammad Aslam; Walid Soufan (Environmental Research, 2024)

Bacillus safensis filtrate-based ZnO nanoparticles control black heart rot disease of apricot fruits by maintaining its soluble sugars and carotenoids - Farhana; Abu Bakr Umer Farooq; Urooj Haroon; Hira Saleem; Mahnoor Akbar; Maryam Anar; Muhammad Nawaz; Hassaan Ateeb Ahmad; Junaid Ahmed; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (World Journal of Microbiology and Biotechnology, 2024)

Sheep bone valorization: Enhancing gastronomic sustainability through hydroxyapatite-enriched potato wedges - Saba Liaqat; Zaheer Ahmed; Muhammad Usama Umer; Qasim Ali; Muhammad Farooq Mustafa; Ifra Ferheen; Muhammad Waseem (International Journal of Gastronomy and Food Science, 2024)

Iron Oxide-Chitosan-Based Nanocomposite for Efficient Fluoride Removal From Drinking Water - Suraya Samejo; Jameel Ahmed Baig; Tasneem Gul Kazi; Hassan Imran Afridi; Saima Perveen; Muhammad Umer Frooq; Khalil Akhtar; Shakoor Ahmed Solangi; Fahad Abbasi; Sajjad Hussain (Water, Air, & Soil Pollution, 2024)

Temporal profiling of physiological, histological, and transcriptomic dissection during auxin-induced adventitious root formation in tetraploid Robinia pseudoacacia micro-cuttings - Saleem Uddin; Muhammad Zeeshan Munir; Eduardo Larriba; José Manuel Pérez-Pérez; Sadia Gull; Tariq Pervaiz; Umer Mahmood; Zahid Mahmood; Yuhan Sun; Yun Li (Planta, 2024)

Zinc-Coated Urea with Gelatin-Enhanced Zinc Biofortification, Apparent Nitrogen Recovery, and Ryegrass Production - Bilal Abdullah; Muhammad Bilal Khan Niazi; Zaib Jahan; Tariq Shah; Umer Shahzad Malik; Bilal Beig; Abid Mahmood; Ghulam Abbas Shah; Zahid Iqbal (Journal of Soil Science and Plant Nutrition, 2024)

Socio-environmental factors and solar housing system adoption: moderating effect of attitude - Ahsen Maqsoom; Muhammad Hammad; Muhammad Umer; Wesam Salah Alaloul; Hassan Ashraf; Muhammad Ali Musarat; Tahira Nazir (Innovative Infrastructure Solutions, 2024)

Algae-derived bioactive compounds as potential pharmaceuticals for cancer therapy: A comprehensive review - Lubna Anjum Minhas; Muhammad Kaleem; Hafiz Muhammad Umer Farooqi; Farzana Kausar; Rooma Waqar; Theophilus Bhatti; Shahid Aziz; Dong Won Jung; Abdul Samad Mumtaz (Algal Research, 2024)

Phytoremediation of heavy metals spiked soil by Celosia argentea L.: effect on plant growth and metal stabilization - Umer Hussain; Rabia Afza; Iram Gul; Muhammad Anwar Sajad; Ghulam Mujtaba Shah; Zahir Muhammad; Shujaul Mulk Khan (Environmental Science and Pollution Research, 2024)

Effective biological control of Lentil (Lens culinaris) Fusarium wilt and plant growth promotion through native Rhizobacteria - Javeria Ayub; Ayesha Tahir; Umer Iqbal; Huma Ayub; Muhammad Zeeshan Hyder; Amna Kiyani; Fauzia Yusuf Hafeez; Muhammad Kashif Ilyas; Abdul Ghafoor; Tayyaba Yasmin (Physiological and Molecular Plant Pathology, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Construction and application of a new watermelon germplasm with the phenotype of dwarf and branchless - Junling Dou; Qishuai Kang; Tengwei Li; Muhammad Jawad Umer; Badr Alharthi; Dongming Liu; Sen Yang; Huanhuan Niu; Changsheng Ma; Huayu Zhu; Luming Yang (Functional & Integrative Genomics, 2023)

Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Saif Haider; Muhammad Umer Masood; Muhammad Rashid; Tauqeer Ali; Chaitanya B. Pande; Fahad Alshehri; Ismail Elkhrachy (Urban Climate, 2023)

A comprehensive study of the sources, extraction methods and structures of the Saponin compounds for its antidiabetic activity - Muhammad Umair Afzal; Muhammad Pervaiz; Anam Ejaz; Eisha Bajwa; Sadaf Naz; Zohaib Saeed; Sami Ullah; Syeda Shaista Gillani; Rana Rashad Mehmood Kan; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Nexuses between carbon emissions, trade openness, transport services, globalization index, and growth in China: targeting the sustainable development goals - Li Huang; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Abdul Haseeb; Muhammad Bashir Khan; Amir Rafique (Environmental Science and Pollution Research, 2023)

Fabrication of a novel nanocomposite (TiO2/WO3/V2O5) by hydrothermal method as catalyst for hazardous waste treatment - Umer Younas; Awais Ahmad; Aftab Islam; Faisal Ali; Muhammad Pervaiz; Aimon Saleem; Muhammad Waseem; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Salman Raza Naqvi (Fuel, 2023)

Hydrothermal synthesis of V2O5/TiO2 decorated graphitic carbon nitride nanocomposite for biomolecule oxidation inhibition and dye degradation applications - Muhammad Waseem; Awais Ahmad; Muhammad Sagir; Umer Younas; Zohaib Saeed; Muhammad Pervaiz; Faisal Ali; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Rama Rao Karri (Environmental Research, 2023)

“Garlic and ginger extracts mediated green synthesis of silver and gold nanoparticles: A review on recent advancements and prospective applications’’ - Zohaib Saeed; Muhammad Pervaiz; Anam Ejaz; Shah Hussain; Shumila Shaheen; Behram Shehzad; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Assessing total erythrocyte count as a potential attribute for estimating hemoglobin in Cholistani cattle - Umer Farooq; Musadiq Idris; Nouman Sajjad; Muhammad Abrar Afzal (Tropical Animal Health and Production, 2023)

Metabolomics Analysis Reveals Soybean Node Position Influence on Metabolic Profile of Soybean Seed at Various Developmental Stages - Dennis Takpah; Muhammad Ahsan Asghar; Ali Raza; Hafiz Hassan Javed; Abd Ullah; Xiangqing Huang; Khansa Saleem; Cong-Wei Xie; Xinli Xiao; Kyei Sarpong Clement; Muhammad Umer Farooq; Wenyu Yang; et al. (Journal of Plant Growth Regulation, 2023)

Life table parameters and feeding potential of Chrysoperla carnea (Stephens) on eggs of Pyrilla perpusilla (Walker) - Muhammad Umer; Javed khan; Fan Fan; Xiaofan Yang; Mengyao Li; Asim Iqbal; Guoshu Wei (Journal of Plant Diseases and Protection, 2023)

Forecasting potential risk for development of spiromesifen resistance in Tetranychus urticae (Koch): its genetics and cross-resistance - Muhammad Kamran; Zahid Mehmood Sarwar; Ayyan Umer; Sarfraz Ali Shad; Muhammad Abubakar (International Journal of Tropical Insect Science, 2023)

Natural occurrence of fungal species on the rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae), in Punjab, Pakistan - Tiyyabah Khan; Hafiz Azhar Ali Khan; Waheed Anwar; Muhammad Rizwan Khan; Muhammad Umer (International Journal of Tropical Insect Science, 2023)

Positive responses of soil nutrients and enzyme activities to AM fungus under interspecific and intraspecific competitions when associated with litter addition - Bangli Wu; Muhammad Umer; Yun Guo; Minhong He; Xu Han; Kaiping Shen; Tingting Xia; Yuejun He; Xinhua He (Rhizosphere, 2023)

Comprehensive insights into the regulatory mechanisms of lncRNA in alkaline-salt stress tolerance in rice - Obaid Ur Rehman; Muhammad Uzair; Muhammad Shahbaz Farooq; Bilal Saleem; Safira Attacha; Kotb A. Attia; Umer Farooq; Sajid Fiaz; Wael. H. El-Kallawy; Itoh Kimiko; Muhammad Ramzan Khan (Molecular Biology Reports, 2023)

Neem and Castor Oil–Coated Urea Mitigates Salinity Effects in Wheat by Improving Physiological Responses and Plant Homeostasis - Imran Khan; Sadia Muhammad Ali; Muhammad Umer Chattha; Lorenzo Barbanti; Roberta Calone; Athar Mahmood; Tasahil S. Albishi; Muhammad Umair Hassan; Sameer H. Qari (Journal of Soil Science and Plant Nutrition, 2023)
Soil salinity is abiotic stress of growing concern, whose effects can be potentially mitigated by the use of suitable fertilisers. Based on this, an experiment was conducted to determine the role of vegetable oil–coated urea on the performance of wheat ( Triticum aestivum ) under salinity. Neem oil–coated urea (NOCU), castor oil–coated urea (COCU), and normal urea (NU) were compared in wheat plants growing in pots at three soil salinity levels (0, 6, and 12 dS m -1 ). Plant morphology, growth, element contents (Na, Cl, K, and N), and several traits were assessed at the flag leaf stage; biological yield, grain yield, and its components were assessed at maturity. Salinity stunted growth (approximately -50% yield with high salinity vs. control); boosted Na and Cl concentrations while abating K and N concentrations in plant organs; impaired leaf water status; reduced photosynthetic pigments and increased antioxidant activities and osmo-regulating compounds. NOCU and, to a lesser degree, COCU mitigated salinity effects by upgrading antioxidant activities, reducing oxidative stress markers, increasing leaf water status, photosynthetic pigments, and osmo-regulating compounds. However, NOCU under high salinity could only achieve the levels of NU under intermediate salinity. Lastly, NOCU and COCU restricted plant entry of adverse ions (Na and Cl) while increasing K and N accumulation. Vegetable oil–coated urea, namely NOCU, significantly contributed to improving wheat behaviour and final yield under salinity. These outcomes are associated with the two fertilisers’ properties of slow nitrogen release.

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

Toxicity assessment of heavy metal (Pb) and its bioremediation by potential bacterial isolates - Usaal Tahir; Mariam Zameer; Qurban Ali; Ayesha Rafique; Syeda Maham Ali; Muhammad Umer Arif; Imtiaz Nawaz; Saif ul Malook; Daoud Ali (Environmental Monitoring and Assessment, 2023)

Histopathology and antibody responses describe the seasonal pattern of dicrocoeliosis in small ruminants in the Himalayan ranges of Pakistan - Muhammad Asim Khan; Kiran Afshan; Umer Chaudhry; Sabika Firasat; Neil D. Sargison (Veterinary Parasitology, 2023)

Effect of exogenous taurine on growth, oxidative defense, and nickel (Ni) uptake in canola (Brassica napus L.) under Ni stress - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2023)

Exploring the nexus between green innovations and green growth in G-7 economies: evidence from wavelet quantile correlation and continuous wavelet transform causality methods - Umer Zaman; Muhammad Zubair Chishti; Touseef Hameed; Muhammad Sohail Akhtar (Environmental Science and Pollution Research, 2023)

Hydrological response under CMIP6 climate projection in Astore River Basin, Pakistan - Zeshan Ali; Mudassar Iqbal; Ihsan Ullah Khan; Muhammad Umer Masood; Muhammad Umer; Muhammad Usama Khan Lodhi; Muhammad Atiq Ur Rehman Tariq (Journal of Mountain Science, 2023)
Climate change strongly influences the available water resources in a watershed due to direct linkage of atmospheric driving forces and changes in watershed hydrological processes. Understanding how these climatic changes affect watershed hydrology is essential for human society and environmental processes. Coupled Model Intercomparison Project phase 6 (CMIP6) dataset of three GCM’s (BCC-CSM2-MR, INM-CM5-0, and MPI-ESM1-2-HR) with resolution of 100 km has been analyzed to examine the projected changes in temperature and precipitation over the Astore catchment during 2020–2070. Bias correction method was used to reduce errors. In this study, statistical significance of trends was performed by using the Man- Kendall test. Sen’s estimator determined the magnitude of the trend on both seasonal and annual scales at Rama Rattu and Astore stations. MPI-ESM1-2-HR showed better results with coefficient of determination (COD) ranging from 0.70–0.74 for precipitation and 0.90–0.92 for maximum and minimum temperature at Astore, Rama, and Rattu followed by INM-CM5-0 and BCC-CSM2-MR. University of British Columbia Watershed model was used to attain the future hydrological series and to analyze the hydrological response of Astore River Basin to climate change. Results revealed that by the end of the 2070s, average annual precipitation is projected to increase up to 26.55% under the SSP1–2.6, 6.91% under SSP2–4.5, and decrease up to 21.62% under the SSP5–8.5. Precipitation also showed considerable variability during summer and winter. The projected temperature showed an increasing trend that may cause melting of glaciers. The projected increase in temperature ranges from - 0.66°C to 0.50°C, 0.9°C to 1.5°C and 1.18°C to 2°C under the scenarios of SSP1–2.6, SSP2–4.5 and SSP5–8.5, respectively. Simulated streamflows presented a slight increase by all scenarios. Maximum streamflow was generated under SSP5–8.5 followed by SSP2–4.5 and SSP1–2.6. The snowmelt and groundwater contributions to streamflow have decreased whereas rainfall and glacier melt components have increased on the other hand. The projected streamflows (2020–2070) compared to the control period (1990–2014) showed a reduction of 3%–11%, 2%–9%, and 1%–7% by SSP1–2.6, SSP2–4.5, and SSP5–8.5, respectively. The results revealed detailed insights into the performance of three GCMs, which can serve as a blueprint for regional policymaking and be expanded upon to establish adaption measures.

Evaluation of Physio-Morphological and Biochemical Responses for Salt Tolerance in Wheat (Triticum aestivum L.) Cultivars - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

Effects of the circular economy, environmental policy, energy transition, and geopolitical risk on sustainable electricity generation - Muhammad Zubair Chishti; Eyup Dogan; Umer Zaman (Utilities Policy, 2023)

Genome-Wide Identification, Characterization, and Expression Profiling of Eukaryotic-Specific UBP Family Genes in Brassica rapa - Umer Karamat; Javaria Tabusam; Muhammad Khalil Ullah Khan; Muhammad Jawad Akbar Awan; Sumer Zulfiqar; Wenchao Du; Muhammad Awais Farooq (Journal of Plant Growth Regulation, 2023)

Genome-wide identification and expression analysis of terpene synthases in Gossypium species in response to gossypol biosynthesis - Teame Gereziher Mehari; Hui Fang; Wenxiang Feng; Yuanyuan Zhang; Muhammad Jawad Umer; Jinlei Han; Allah Ditta; Muhammad K. R. Khan; Fang Liu; Kai Wang; Baohua Wang (Functional & Integrative Genomics, 2023)

Insights to Gossypium defense response against Verticillium dahliae: the Cotton Cancer - Muhammad Jawad Umer; Jie Zheng; Mengying Yang; Raufa Batool; Aamir Ali Abro; Yuqing Hou; Yanchao Xu; Haileslassie Gebremeskel; Yuhong Wang; ZhongLi Zhou; Xiaoyan Cai; Fang Liu; et al. (Functional & Integrative Genomics, 2023)

Assessment of formulation variables of poor water soluble diacerein for its improved loading and anti-inflammatory activity - Maryam Shabbir; Kashif Barkat; Muhammad Umer Ashraf; Uzair Nagra; Syed Nisar Hussain Shah (Drug Delivery and Translational Research, 2023)

Negative Impact of Unstable Spiromesifen Resistance on Fitness of Tetranychus urticae (Acari: Tetranychidae) - Muhammad Abubakar; Ayyan Umer; Sarfraz Ali Shad; Zahid Mehmood Sarwar; Muhammad Kamran (Neotropical Entomology, 2023)

Corrigendum to “The role of renewable energy and natural resources for sustainable agriculture in ASEAN countries: Do carbon emissions and deforestation affect agriculture productivity?” [Resour. Pol. (2022) 102578] - Ritika Chopra; Cosimo Magazzino; Muhammad Ibrahim Shah; Gagan Deep Sharma; Amar Rao; Umer Shahzad (Resources Policy, 2023)

RETRACTED: Recent developments in metal/metalloid nanomaterials for battery applications; a comparative review - Awais Ahmad; Shumila Shaheen; Saadat Majeed; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Sufyan Javed; Rafael Luque; Lalitha Gnanasekaran (Fuel, 2023)

Vegetable oils as bio-based precursors for epoxies - Fareeha Marriam; Adnan Irshad; Isra Umer; Muhammad Arslan Asghar; Muhammad Atif (Sustainable Chemistry and Pharmacy, 2023)

A systematic and critical review on effective utilization of artificial intelligence for bio-diesel production techniques - Junaid Ahmad; Muhammad Awais; Umer Rashid; Chawalit Ngamcharussrivichai; Salman Raza Naqvi; Imtiaz Ali (Fuel, 2023)

Moving towards sustainability: how do low-carbon energy, current account balance, and reserves induce environmental deterioration in the Big 3? - Mubeen Abdur Rehman; Muhammad Umer Quddoos; Muhammad Sajid Amin; Ghulam Ghouse (Environmental Science and Pollution Research, 2023)

RETRACTED: A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites - Awais Ahmad; Mushkbar Zahra; Fakhar e Alam; Shafaqat Ali; Muhammad Pervaiz; Zohaib Saeed; Umer Younas; Muhammad Mushtaq; Saravanan Rajendran; Rafael Luque (Fuel, 2023)

Watermelon domestication was shaped by stepwise selection and regulation of the metabolome - Pingli Yuan; Congping Xu; Nan He; Xuqiang Lu; Xingping Zhang; Jianli Shang; Hongju Zhu; Chengsheng Gong; Hanhui Kuang; Tang Tang; Yong Xu; Shuangwu Ma; et al. (Science China Life Sciences, 2023)

Experimental Characterization-Based Machine Learning Modeling for the Estimation of Geotechnical Properties of Clay Liners - Hafiz Muhammad Awais Rashid; Muhammad Sufyan; Atif Ismail; Umer Waqas (Geotechnical and Geological Engineering, 2023)

Spatial Distribution of Dicrocoelium in the Himalayan Ranges: Potential Impacts of Ecological Niches and Climatic Variables - Muhammad Asim Khan; Kiran Afshan; Neil D. Sargison; Martha Betson; Sabika Firasat; Umer Chaudhry (Acta Parasitologica, 2023)
Purpose Dicrocoeliosis can be an important cause of production loss in ruminants due to the cost of liver condemnation at slaughter. The aim of the present study was to determine the prevalence of Dicrocoelium infection and to predict the ecological niches and climatic variables that support dicrocoeliosis in the Himalayan ranges of Pakistan. Methods and Results Dicrocoelium was detected in 33 of 381 liver samples and 238 of 6060 blood samples taken from sheep and goat herds in the area. The prevalence of dicrocoeliosis was higher in sheep than in goats and highest in females aged more than 3 years. An environmental risk map was created to predict active zones of transmission and showed the highest probability values in central parts of the Chitral district in the northwest of Pakistan. Climatic variables of the mean monthly diurnal temperature range (Bio2), annual precipitation (Bio12), and normalised difference vegetation index (NDVI) were found to be significantly ( p Dicrocoelium infection. Conclusion Together, the findings of this study demonstrate the most suitable ecological niches and climatic variables influencing the risk of dicrocoeliosis in the Himalayan ranges of Pakistan. The methods and results could be used as a reference to inform the control of dicrocoeliosis in the region.

Recyclable Cu–Ag bimetallic nanocatalyst for radical scavenging, dyes removal and antimicrobial applications - Faisal Ali; Sadia Akbar; Mika Sillanpaa; Umer Younas; Adnan Ashraf; Muhammad Pervaiz; Rizwan Kausar; Ikram Ahmad; Asma A. Alothman; Mohamed Ouladsmane (Chemosphere, 2023)

Green synthesis of graphene-based metal nanocomposite for electro and photocatalytic activity; recent advancement and future prospective - Shumila Shaheen; Zohaib Saeed; Awais Ahmad; Muhammad Pervaiz; Umer Younas; Rana Rashad Mahmood Khan; Rafael Luque; Saravanan Rajendran (Chemosphere, 2023)

Downregulation of NF-κB activation pathways using essential oil derived from Citrus pseudolimon: Anticancer and anti-inflammatory potential - Arfaa Sajid; Qaisar Manzoor; Anam Sajid; Arif Nazir; Muhammad Arsalan Mumtaz; Najum Fatima; Samar Zuhair Alshawwa; Munawar Iqbal; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Expansion of human amniotic epithelial cells using condition cell reprogramming technology - Aisha Naeem; Muhammad Umer Choudhry; Alex Kroemer; Simone Wahnschafft; Wanxing Cui; Chris Albanese (Human Cell, 2022)
Human amniotic epithelial cells (hAECs) are non-immunogenic epithelial cells that can develop into cells of all three germline lineages. However, a refined clinically reliable method is required to optimize the preparation and banking procedures of hAECs for their successful translation into clinical studies. With the goal of establishing standardized clinically applicable hAECs cultured cells, we described the use of a powerful epithelial cell culture technique, termed C onditionally R eprogrammed Cells (CRC) for ex vivo expansion of hAECs. The well-established CRC culture method uses a Rho kinase inhibitor (Y-27632) and J2 mouse fibroblast feeder cells to drive the indefinite proliferation of all known epithelial cell types. In this study, we used an optimized CRC protocol to successfully culture hAECs in a CRC medium supplemented with xenogen-free human serum. We established that hAECs thrive under the CRC conditions for over 5 passages while still expressing pluripotent stem markers (OCT-4, SOX-2 and NANOG) and non-immunogenic markers (CD80, CD86 and HLA-G) suggesting that even late-passage hAECs retain their privileged phenotype. The hAECs-CRC cells were infected with a puromycin-selectable lentivirus expressing luciferase and GFP (green fluorescent protein) and stably selected with puromycin. The hAECs expressing GFP were injected subcutaneously into the flanks of Athymic and C57BL6 mice to check the tolerability and stability of cells against the immune system. Chemiluminescence imaging confirmed the presence and viability of cells at days 2, 5, and 42 without acute inflammation or any tumor formation. Collectively, these data indicate that the CRC approach offers a novel solution to expanding hAECs in humanized conditions for future clinical uses, while retaining their primary phenotype. Graphical abstract

Trehalose: a promising osmo-protectant against salinity stress—physiological and molecular mechanisms and future prospective - Muhammad Nawaz; Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Adnan Noor Shah; Mohamed Hashem; Saad Alamri; Maria Batool; Adnan Rasheed; Maryam A. Thabit; Haifa A. S. Alhaithloul; Sameer H. Qari (Molecular Biology Reports, 2022)

Measurement and identification of relative poverty level of pastoral areas: an analysis based on spatial layout - Haiying Lin; Youhan Gao; Tianqi Zhu; Huayuan Wu; Pengshen Hou; Wenlong Li; Shuxia Hou; Muhammad Umer Arshad (Environmental Science and Pollution Research, 2022)
Pastoral areas are the key difficulty in China’s pursuit of common prosperity and a key region for China to build the northern ecological safety barrier and to realize the Two Centenary Goals. It is of great significance to scientifically evaluate the quality of rural life (QRL), measure the relative poverty level (RPL), and identify the relatively poor areas, making it possible to dock poverty elimination with rural revitalization. Based on the socio-economic data of 18 pastoral areas in Inner Mongolia, this paper draws on spatial layout theory to evaluate QRL and measures RPL by the natural breakpoint method and then identifies the relatively poor areas in Inner Mongolia. The results show that (1) the QRLs of pastoral areas in Inner Mongolia were unbalanced and highly polarized. The mean score of QRLs was 0.2598. Eleven (61.11%) of the counties/banners had a QRL smaller than the mean score. On the spatial layout of QRLs, the western areas were stronger than the central areas. High QRL counties/banners are mainly concentrated in the western region. In the central region, the QRLs were very fragmented, falling onto all five levels. (2) The pastoral areas in Inner Mongolia differed significantly in RPL. The mean score of RPL stood at 0.3788. Nine counties/banners (50%) had an RPL greater than the mean. Contrary to the spatial layout features of QRLs, the central pastoral areas in Inner Mongolia had stronger RPLs than the eastern ones. High RPL counties/banners are mostly clustered in the central region. The spatial layout of RPLs is relatively reasonable in the central region: the RPLs decreased gradually from Dorbod Banner. (3) Nearly 45% of the pastoral areas in central and western Inner Mongolia face serious relative poverty and a high risk of returning to poverty. Eight counties/banners (45%) were identified as high composite relative poverty areas. From spatial layout, the composite relatively poor counties/banners clustered clearly, mainly in the western region. Finally, this paper establishes a warning mechanism against large-scale returning to poverty, aiming to lower composite RPL. The research results provide empirical reference and implementation path for consolidating the results of poverty eradication and facilitating rural revitalization.

Re-examining the nexuses of communicable diseases, environmental performance, and dynamics of sustainable Development in OECD countries - Zhang Yu; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Muhammad Sajid Amin; Laeeq Razzak; Muhammad Tariq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Nanotechnology-based controlled release of sustainable fertilizers. A review - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Umer Shahzad Malik; Mohammad Daud Khan; Juliana Heloisa Pinê Américo-Pinheiro; Dai-Viet N. Vo (Environmental Chemistry Letters, 2022)
The rising population is increasing food demand, yet actual crop production is limited by the poor efficiency of classical fertilizers. In particular, only about 40–60% of fertilizer nitrogen, 15–20% of phosphorus and 50–60% of potassium are used by crop plants, the rest ending polluting the environment. Nanofertilizers are promising alternatives. Here, we review plant nutrients, synthesis of zinc oxide nanoparticles, encapsulation of nanoparticles in fertilizers, and effect on plants.

Phytochemicals targeting NAFLD through modulating the dual function of forkhead box O1 (FOXO1) transcription factor signaling pathways - Usman Sabir; Hafiz Muhammad Irfan; Alamgeer; Ihtisham Umer; Zahid Rasul Niazi; Hafiz Muhammad Mazhar Asjad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

RETRACTED ARTICLE: Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Maria Khalil; Muhammad Asif Hanif; Umer Rashid; Junaid Ahmad; Ali Alsalme; Toshiki Tsubota (Environmental Science and Pollution Research, 2022)

Hydrogen peroxide priming alleviates salinity induced toxic effect in maize by improving antioxidant defense system, ionic homeostasis, photosynthetic efficiency and hormonal crosstalk - Muhammad Umer Chattha; Muhammad Uzair Ul Hassan; Imran Khan; Muhammad Nawaz; Adnan Noor Shah; Abdul Sattar; Mohamed Hashem; Saad Alamri; Muhammad Talha Aslam; Haifa A. S. Alhaithloul; Muhammad Umair Hassan; Sameer H. Qari (Molecular Biology Reports, 2022)

Design and Optimization of Novel Taste-Masked Medicated Chocolates of Dextromethorphan with In vitro and In vivo Taste Evaluation - Rahat Fatima Naqvi; Ahmad Khan; Muhammad Farooq Umer; Obaidullah Malik; Nisar Ahmad Shahwani (Journal of Pharmaceutical Innovation, 2022)

Performance of Wheat Cultivars Under Different Tillage and Crop Establishment Methods - Muhammad Mahmood Iqbal; Imran Khan; Muhammad Umer Chattha; Muhammad Umair Hassan; Muhammad Iqbal; Muhammad Farooq (International Journal of Plant Production, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Assessment of cadmium and lead tolerance potential of quinoa (Chenopodium quinoa Willd) and its implications for phytoremediation and human health - Muhammad Amjad; Muhammad Mohsin Iqbal; Ghulam Abbas; Abu Bakar Umer Farooq; Muhammad Asif Naeem; Muhammad Imran; Behzad Murtaza; Muhammad Nadeem; Sven-Erik Jacobsen (Environmental Geochemistry and Health, 2022)

Effects of diverse irrigation with wastewater in soil and plants: assessing the risk of metal to the animal food chain - Zafar Iqbal Khan; Fatima Ghulam Muhammad; Kafeel Ahmad; Shahzad Akhtar; Muhammad Sohail; Muhammad Nadeem; Shahzadi Mahpara; Muhammad Umer Farooq Awan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Does economic complexity matter for environmental sustainability? Using ecological footprint as an indicator - Muhammad Zahid Rafique; Abdul Majeed Nadeem; Wanjun Xia; Majid Ikram; Hafiz Muhammad Shoaib; Umer Shahzad (Environment, Development and Sustainability, 2022)

Preparation and Quality Attributes of Egg-reduced Pound Cake Incorporating Grass Carp ( Ctenopharyngodonidella ) Protein Concentrate - Sohail Khan; Haroon Shah; Sajid Kamal; Abdur Rehman; Qayyum Shehzad; Umer Karamat; Aiman Karim; Mudassar Hussain; Muhammad Muneeb; Wenshui Xia (Journal of Aquatic Food Product Technology, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Review of hospital plastic waste management strategies for Pakistan - Yasir Qayyum Gill; Mudasar Khurshid; Umer Abid; Muhammad Wajid Ijaz (Environmental Science and Pollution Research, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Nano-structured dynamic Schiff base cues as robust self-healing polymers for biomedical and tissue engineering applications: a review - Umer Shahzad Malik; Muhammad Bilal Khan Niazi; Zaib Jahan; Mazhar Iqbal Zafar; Dai-Viet N. Vo; Farooq Sher (Environmental Chemistry Letters, 2022)
Polymer materials are vulnerable to damages, failures, and degradations, making them economically unreliable. Self-healing polymers, on the other hand, are multifunctional materials with superior properties of autonomic recovery from physical damages. These materials are suitable for biomedical and tissue engineering in terms of cost and durability. Schiff base linkages-based polymer materials are one of the robust techniques owing to their simple self-healing mechanism. These are dynamic reversible covalent bonds, easy to fabricate at mild conditions, and can self-reintegrate after network disruption at physiological conditions making them distinguished. Here we review self-healing polymer materials based on Schiff base bonds. We discuss the Schiff base bond formation between polymeric networks, which explains the self-healing phenomenon. These bonds have induced 100% recovery in optimal cases.

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Ameliorative effect of ethoxylated chalcone-based MAO-B inhibitor on behavioural predictors of haloperidol-induced Parkinsonism in mice: evidence of its antioxidative role against Parkinson’s diseases - Naseer Maliyakkal; Uzma Saleem; Fareeha Anwar; Muhammad Ajmal Shah; Bashir Ahmad; Filzah Umer; Mohammad Ali Abdullah Almoyad; Della Grace Thomas Parambi; Asmy Appadath Beeran; Lekshmi R Nath; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Integrated support vector regressor and hybrid neural network techniques for earthquake prediction along Chaman fault, Baluchistan - Umer Khalil; Bilal Aslam; Zaheer Abbas Kazmi; Ahsen Maqsoom; Muhammad Irshad Qureshi; Sheheryar Azam; Ahsan Nawaz (Arabian Journal of Geosciences, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Striving towards environmental sustainability: how natural resources, human capital, financial development, and economic growth interact with ecological footprint in China - Sayma Zia; Mustaghis ur Rahman; Mohammed Hassan Noor; Muhammad Kamran Khan; Munaza Bibi; Danish Iqbal Godil; Muhammad Umer Quddoos; Muhammad Khalid Anser (Environmental Science and Pollution Research, 2021)

Traditional and cultural uses of medicinal plant species in the flora of Kuz Abakhel, for the treatment of various ailments - Noor Muhammad; Nisar Uddin; Muhammad Khalil Ullah Khan; Muhammad Umer; Niaz Ali; Shariat Ullah (Advances in Traditional Medicine, 2021)

An integrated transcriptome and metabolome approach reveals the accumulation of taste-related metabolites and gene regulatory networks during watermelon fruit development - Chengsheng Gong; Hongju Zhu; Xuqiang Lu; Dongdong Yang; Shengjie Zhao; Muhammad Jawad Umer; Nan He; Pingli Yuan; Muhammad Anees; Weinan Diao; M. O. Kaseb; Wenge Liu (Planta, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Heat stress in cultivated plants: nature, impact, mechanisms, and mitigation strategies—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Lorenzo Barbanti; Muhammad Aamer; Muhammad Mehmood Iqbal; Muhammad Nawaz; Athar Mahmood; Abid Ali; Muhammad Talha Aslam (Plant Biosystems, 2021)

Application of precipitation products for flood modeling of transboundary river basin: a case study of Jhelum Basin - Muhammad Umer; Hamza Farooq Gabriel; Sajjad Haider; Ammara Nusrat; Muhammad Shahid; Muhammad Umer (Theoretical and Applied Climatology, 2021)

Prediction Modeling for the Estimation of Dynamic Elastic Young’s Modulus of Thermally Treated Sedimentary Rocks Using Linear–Nonlinear Regression Analysis, Regularization, and ANFIS - Umer Waqas; Muhammad Farooq Ahmed (Rock Mechanics and Rock Engineering, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

Influence of metallic species for efficient photocatalytic water disinfection: bactericidal mechanism of in vitro results using docking simulation - Aaima Iftikhar; Muhammad Saqib Khan; Umer Rashid; Qaisar Mahmood; Habiba Zafar; Muhammad Bilal; Nadia Riaz (Environmental Science and Pollution Research, 2020)

Climate change impacts and adaptations for wheat employing multiple climate and crop modelsin Pakistan - Jamshad Hussain; Tasneem Khaliq; Senthold Asseng; Umer Saeed; Ashfaq Ahmad; Burhan Ahmad; Ishfaq Ahmad; Muhammad Fahad; Muhammad Awais; Asmat Ullah; Gerrit Hoogenboom (Climatic Change, 2020)

Growth, Biomass Production, and Yield Potential of Quinoa (Chenopodium quinoa Willd.) as Affected by Planting Techniques Under Irrigated Conditions - Saif Ali; Muhammad Umer Chattha; Muhammad Umair Hassan; Imran Khan; Muhammad Bilal Chattha; Babar Iqbal; Muzammal Rehman; Muhammad Nawaz; Muhammad Zubair Amin (International Journal of Plant Production, 2020)

Microfacies, diagenesis and hydrocarbon potential of Eocene carbonate strata in Pakistan - Umer Khitab; Muhammad Umar; Muhammad Jamil (Carbonates and Evaporites, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

Classification of the intact carbonate and silicate rocks based on their degree of thermal cracking using discriminant analysis - Umer Waqas; M. Farooq Ahmed; Muhammad Arshad (Bulletin of Engineering Geology and the Environment, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

2D numerical modeling of two dam-break flood model studies in an urban locality - Sajjad Haider; Umer Saeed; Muhammad Shahid (Arabian Journal of Geosciences, 2020)

Impact of selenium, zinc and their interaction on key enzymes, grain yield, selenium, zinc concentrations, and seedling vigor of biofortified rice - Hla Hla Ei; Tengda Zheng; Muhammad Umer Farooq; Rui Zeng; Yang Su; Yujie Zhang; Yuanke Liang; Zhichen Tang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2020)

Valorization of solid waste biomass by inoculation for the enhanced yield of biogas - Yasir Abbas; Farrukh Jamil; Sikander Rafiq; Moinuddin Ghauri; M. Shahzad Khurram; Muhammad Aslam; Awais Bokhari; Abrar Faisal; Umer Rashid; Sining Yun; Muhammad Mubeen (Clean Technologies and Environmental Policy, 2020)

Composted Sugarcane By-product Press Mud Cake Supports Wheat Growth and Improves Soil Properties - Muhammad Umer Chattha; Muhammad Umair Hassan; Lorenzo Barbanti; Muhammad Bilal Chattha; Imran Khan; Muhammad Usman; Abid Ali; Muhammad Nawaz (International Journal of Plant Production, 2019)

The paradox in accumulation behavior of cadmium and selenium at different planting times in rice - Muhammad Umer Farooq; Jianqing Zhu (Environmental Science and Pollution Research, 2019)

Foliar uptake of arsenic nanoparticles by spinach: an assessment of physiological and human health risk implications - Natasha; Muhammad Shahid; Camille Dumat; Sana Khalid; Faiz Rabbani; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Abbas; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Over 100 years of faults interaction, stress accumulation, and creeping implications, on Chaman Fault System, Pakistan - Muhammad Shahid Riaz; Shan Bin; Shahid Naeem; Wang Kai; Zujun Xie; Syed Mushhad M. Gilani; Umer Ashraf (International Journal of Earth Sciences, 2019)

Alterations in transcriptome and antioxidant activity of naturally aged mice exposed to selenium-rich rice - Rui Zeng; Yuanke Liang; Muhammad Umer Farooq; Yujie Zhang; Hla Hla Ei; Zhichen Tang; Tengda Zheng; Yang Su; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2019)

Effect of male sterile and fertile cytoplasm on nuclear DNA methylation in hybrid rice - Asif Ali; Yun Li; Hui Chen; Peizhou Xu; Hongyu Zhang; Xiaoqiong Chen; Liao Yongxiang; Shaohong Fu; Tingkai Wu; Muhammad Zafar Iqbal; Muhammad Umer Farooq; Xianjun Wu (Acta Physiologiae Plantarum, 2019)

Nickel toxicity in plants: reasons, toxic effects, tolerance mechanisms, and remediation possibilities—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Muhammad Aamer; Muhammad Nawaz; Abid Ali; Muhammad Aman Ullah Khan; Tahir Abbas Khan (Environmental Science and Pollution Research, 2019)

The impact of carbon emission and forest activities on health outcomes: empirical evidence from China - Muhammad Umar Farooq; Umer Shahzad; Suleman Sarwar; Li ZaiJun (Environmental Science and Pollution Research, 2019)

Comparative effect of organic amendments on physio-biochemical traits of young and old bean leaves grown under cadmium stress: a multivariate analysis - Muhammad Shahid; Saliha Shamshad; Abu Bakar Umer Farooq; Marina Rafiq; Sana Khalid; Camille Dumat; Yongqing Zhang; Imtyaz Hussain; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Effect of biofertilizers and diatomaceous earth on life and movement of subterranean termites under laboratory conditions - Sohail Ahmed; Babar Hassan; Muhammad Umer Farooq (International Journal of Tropical Insect Science, 2018)

CO2 foam for enhanced oil recovery (EOR) applications using low adsorption surfactant structure - Muhammad Sagir; Muhammad Mushtaq; Muhammad Bilal Tahir; Muhammad Suleman Tahir; Sami Ullah; Khurum Shahzad; Umer Rashid (Arabian Journal of Geosciences, 2018)

Effect of heat treatment on dynamic properties of selected rock types taken from the Salt Range in Pakistan - M. Farooq Ahmed; Umer Waqas; Muhammad Arshad; J. David Rogers (Arabian Journal of Geosciences, 2018)

Yield Forecasting of Spring Maize Using Remote Sensing and Crop Modeling in Faisalabad-Punjab Pakistan - Ishfaq Ahmad; Umer Saeed; Muhammad Fahad; Asmat Ullah; M. Habib ur Rahman; Ashfaq Ahmad; Jasmeet Judge (Journal of the Indian Society of Remote Sensing, 2018)

LC-MS/MS-based determination of chloramphenicol, thiamphenicol, florfenicol and florfenicol amine in poultry meat from the Punjab-Pakistan - Muhammad Imran; Fazal-e- Habib; Saima Majeed; Abdul Tawab; Waqar Rauf; Moazur Rahman; Muhammad Umer; Mazhar Iqbal (Food Additives & Contaminants: Part A, 2018)

Determination of groundwater potential by using geoelectrical method and petrographic analysis in Rawalakot and adjacent areas of Azad Kashmir, sub-Himalayas, Pakistan - Abrar Niaz; Muhammad Rustam Khan; Umer Ijaz; Muhammad Yasin; Fahad Hameed (Arabian Journal of Geosciences, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Performance of sorghum cultivars for biomass quality and biomethane yield grown in semi-arid area of Pakistan - Muhammad Umair Hassan; Muhammad Umer Chattha; Athar Mahmood; Shahbaz Talib Sahi (Environmental Science and Pollution Research, 2018)

Exhaust emission profiling of fatty acid methyl esters and NOx control studies using selective synthetic and natural additives - Saad Afzal; Muhammad Waseem Mumtaz; Umer Rashid; Muhammad Danish; Muhammad Asam Raza; Ahtasham Raza; Hamid Mukhtar; Saud Ibrahim Al-Resayes (Clean Technologies and Environmental Policy, 2018)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Dietary mycotoxins binders: a strategy to reduce aflatoxin m1 residues and improve milk quality of lactating Beetal goats - Haq Aman Ullah; Aneela Zameer Durrani; Muhammad Ijaz; Aqeel Javeed; Umer Sadique; Zahoor Ul Hassan; Altaf Ur Rahman; Muqader Shah; Irfan Khattak (Journal of Consumer Protection and Food Safety, 2016)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Molecular characterization of infectious bursal disease viruses from Pakistan - Muhammad Zubair Shabbir; Muhammad Ali; Muhammad Abbas; Umer Naveed Chaudhry; Zia-ur-Rehman; Muhammad Munir (Archives of Virology, 2016)

OpenDA-NEMO framework for ocean data assimilation - Nils van Velzen; Muhammad Umer Altaf; Martin Verlaan (Ocean Dynamics, 2016)

Risk factors associated with Mycobacterium bovis skin positivity in cattle and buffalo in Peshawar, Pakistan - Irfan Khattak; Muhammad Hassan Mushtaq; Mansur ud Din Ahmad; Muhammad Sarwar Khan; Mamoona chaudhry; Umer Sadique (Tropical Animal Health and Production, 2016)

Investigation of temporal change in glacial extent of Chitral watershed using Landsat data - Usman Ali Naeem; Muhammad Ali Shamim; Naeem Ejaz; Habib ur Rehman; Umer Mustafa; Hashim Nisar Hashmi; Abdul Razzaq Ghumman (Environmental Monitoring and Assessment, 2016)

Effect of pH on the static adsorption of foaming surfactants on Malaysian sandstone - Muhammad Mushtaq; Isa M. Tan; Umer Rashid; Muhammad Sagir; Mudassar Mumtaz (Arabian Journal of Geosciences, 2015)

Application of GIS for the identification and demarcation of selective heavy metal concentrations in the urban groundwater - Sobia Ashraf; Farhat Abbas; Muhammad Ibrahim; Umer Rashid; Shoaib Khalid; Hammad Raza Ahmad; Khalid Rehman Hakeem; Tahir Majeed (Journal of Geographical Sciences, 2015)

Synthesis, docking studies, and in silico ADMET predictions of some new derivatives of pyrimidine as potential KSP inhibitors - Umer Rashid; Syed Fahad Hassan; Samina Nazir; Abdul Wadood; Muhammad Waseem; Farzana Latif Ansari (Medicinal Chemistry Research, 2015)

Synthesis, characterization antibacterial and antifungal activity of some transition metal complexes - Wajid Rehman; Zonera Hassan; Umer Rashid; Fazal Rahim; Obaid-Ur-Rahman Abid; Muhammad Waseem (Medicinal Chemistry Research, 2014)

Simultaneous perturbation stochastic approximation for tidal models - Muhammad Umer Altaf; Arnold W. Heemink; Martin Verlaan; Ibrahim Hoteit (Ocean Dynamics, 2011)

Enhanced resistance against bacterial wilt in transgenic tomato (Lycopersicon esculentum) lines expressing the Xa21 gene - Amber Afroz; Zubeda Chaudhry; Umer Rashid; Ghulam Muhammad Ali; Farhat Nazir; Javaid Iqbal; Muhammad Rashid Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)